A Process‐Structure Investigation of Aluminum Oxide and Oxycarbide Thin Films prepared by Direct Liquid Injection CVD of Dimethylaluminum Isopropoxide (DMAI)1 . Issue 10 (10th November 2015) - Baggetto, Loïc; Charvillat, Cédric; Esvan, Jérôme; Thébault, Yannick; Samélor, Diane; Vergnes, Hugues; Caussat, Brigitte; Gleizes, Alain; Vahlas, Constantin
Abstract: We present the direct liquid injection CVD of aluminum oxide and oxycarbide thin films using dimethylaluminum isopropoxide at high process temperature (500–700 °C) with the addition of O2 gas, and at low temperature (150–300 °C) with the addition of H2 O vapor. Very smooth films with typical roughness values lower than 2 nm are obtained. The thin films are composed of an amorphous material. The composition evolves as a function of temperature from that of a partial hydroxide to a stoichiometric oxide at low deposition temperature (150–300 °C), and from that of a stoichiometric oxide to a mixture of an oxide with an (oxy) carbide at higher temperature (500–700 °C). Abstract : The DLI CVD of aluminum oxide and oxycarbide thin films using dimethylaluminum isopropoxide at high process temperature with O2 gas and at low temperature with H2 O vapor is presented. Tuning the process conditions (temperature, co‐reactant) allows to control the composition and film properties to obtain partially hydroxylated alumina, stoichiometric alumina or oxycarbide materials.